O processo de ensino-aprendizagem de libras por meio do moodle da UAB-UFSCar - Campos, Mariana de Lima Isaac Leandro (2015)
The development of Libras teaching-learning conditions for distance education is necessary in the Universidade Federal de São Carlos (Ufscar) and other higher education institutions. It is pivotal discussing the topic since there are few researches about it. This study presents the researches and analyses of Libras teaching-learning aspects as a second language in distance education by Learning Management System (LMS) and via Moodle. To that end, the research considered the environment suitableness and the communication and interaction processes between the LMS agents (students, tutors and professors). A mixed method (qualitative and quantitative) was applied to on-line questionnaires regarding the Libras I course from the Education and Musical Education departments in UAB-Ufscar. Further, the agents’ opinions and perceptions concerning the tools, the pedagogical procedures and the learning/teaching interaction were analyzed. The analysis was based on Bakhtin’s theoretical assumptions regarding the fundamental dialogical interactions in the language teaching-learning process, which was applied to Libras in this study. The subjects surveyed were 103 students (whose data were clustered in Study 1); 9 virtual tutors (whose data were clustered in Study 2) and 3 professors (whose data were clustered in Study 3). A protocol was set up to analyze this data and according to it, for Study 1, the data was organized and split in the following categories: a) Tools; b) Pedagogical procedures; c) Learning aspects. For Study 2: a) Virtual tutoring experiences; b) LMS tools; c) Interaction and learning. For Study 3: a) Virtual teaching experiences; b) Distance interaction with students. The opinions and perceptions regarding different items got good ratings by the LMS agents and the course, in general, seems to have reached its goals. The researchers analyzed the propositions shown by the agents and they indicate an enhancement of Libra courses in order to make them more accessible to hearing students.